8 - Pratiques et logiques de l'épargne collective chez les migrants maliens et sénégalais en France: 10.4314/ad.v27i1.22155 - Dieng, Seydi Ababacar (Africa Development, 2002)
Malian and Senegalese emigrants resident in France have set up and developed collective structures in the form of tontines and associations. As community networks of financial, economic and social solidarity, these structures are reinforced through mutual help and solidarity, the intrinsic values of African societies - based on mutual recognition and reciprocal relationships. Like the groups in the countries of origin, these structures often bring together closely-related emigrants. The existence and operation of these structures demand a strong financial base and the establishment of a collective savings scheme. Depending on the specific objective of each structure, the collective savings scheme serves as a means of social protection, mutual help among members, or as a mechanism for economic and social development of their local communities of origin.